Perkembangan dan Prospek Komoditas Pangan Segar Asal Tumbuhan (PSAT) di Indonesia - Mufidah, Norma; Hidayat, Syarif Imam; Rizkiyah, Noor (Universitas Galuh, 2025)
ABSTRACT Fresh Food of Plant Origin (PSAT) is an important commodity that supports national food security and has a strategic role in meeting the nutritional needs of the community. As an agrarian country, Indonesia has great potential in the development of PSAT, but challenges such as land conversion, price fluctuations, and low productivity are still obstacles. This study aims to analyze the development and prospects of Fresh Food of Plant Origin (PSAT) commodities in Indonesia with a focus on strategic commodities, namely rice, corn, and soybeans. The method used includes time series data analysis with the ARIMA model to predict PSAT production trends until 2045. PSAT commodities include rice, corn and soybeans. The secondary data analyzed includes production data from 2002 to 2022 obtained from 34 provinces in Indonesia. The results of the study show that the distribution of PSAT commodities in Indonesia when viewed from the production of areas that have an increasing development tendency throughout 2019-2022 is the Java archipelago. The results of the development trend and prospects of PSAT commodities in Indonesia based on ARIMA analysis stated that the forecast for PSAT commodity production from 2022-2045 continues to increase, especially in rice and corn commodities. Therefore, strategic policies such as land protection, provision of agricultural technology, and improvement of distribution efficiency are needed to ensure the sustainability of PSAT production.